BUDAYA KONSUMSI KAUM SANTRI DI TENGAH RUANG KOTA - M. Alie Humaedi (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2013)
The making image of cultural pradices of santri in the City of Kudus is very unique; it is a mixture of the modern consumtive culture and traditional productive culture. The accommodative form of both cultures has influenced the. symbols of traditional city, considered as the saint city, which has many religious meanings. Mall Kudus means not only as the centre of consumptive economy, but also as the cultural centre that tries to meet traditional and modern elements in their covers. Santri, then, becotnes a groupf of people who enjoy best this condition. This article tries to answer the main question about the position of Mall Kudus in the process of the formation of comsumtive culutre of Santri. After collecting data by using interoiews, observation, and documentation, and analyzing by using qualitative explanatory method, this research shows the relationship between the maagement of urban space and the formation of cousumtive culture of santri. This conclusion is based on the aspect of the management of urban spaces, especially the building of Mall, which exspressively creates the consumtive culture of the santri; even the traditional santri. Key Words: Consumptive Culture, City Symbol, Mal Kudus, Santri